2005
DOI: 10.1111/j.1745-6584.2005.0018.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in ground water chemistry at a phytoremediation demonstration site

Abstract: A field-scale demonstration project was conducted to evaluate the capability of eastern cottonwood trees (Populus deltoides) to attenuate trichloroethene (TCE) contamination of ground water. By the middle of the sixth growing season, trees planted where depth to water was <3 m delivered enough dissolved organic carbon to the underlying aquifer to lower dissolved oxygen concentrations, to create iron-reducing conditions along the plume centerline and sulfate-reducing or methanogenic conditions in localized area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The data suggest that the decrease of PCE concentration was due to reductive dechlorination of PCE mainly to TCE, but also to cis-DCE and VC, which was apparently not an active process in the unplanted control. Field studies have reported the increased transformation of TCE in a planted field site compared to unplanted areas (Eberts et al, 2005). The results suggested that the presence of root exudates led to the eventual creation of sulfate-reducing and methanogenic conditions and an increase in the rate of reductive dechlorination of TCE in the groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggest that the decrease of PCE concentration was due to reductive dechlorination of PCE mainly to TCE, but also to cis-DCE and VC, which was apparently not an active process in the unplanted control. Field studies have reported the increased transformation of TCE in a planted field site compared to unplanted areas (Eberts et al, 2005). The results suggested that the presence of root exudates led to the eventual creation of sulfate-reducing and methanogenic conditions and an increase in the rate of reductive dechlorination of TCE in the groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…The rhizosphere can be sufficiently reducing to support microbial reductive dehalogenation activity in anaerobic zones created by the combination of plant root–cell metabolism and the aerobic degradation of root exudates in the rhizosphere (Eberts et al, 2005; Hojberg et al, 1999). The presence of cis-DCE and VC in the effluent water, which are known metabolites of microbial dehalogenation, but not plant activity, suggests that microbial dehalogenation was active at our site and contributed to contaminant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…This result is unexpected because there are many more evidences showing that the environment around the roots are more aerobic, so that one could predict less HCB degradation in the root zone (Brix, 1997;Stottmeister et al, 2003;Wei et al, 2003). In the anaerobic environments required for HCB degradation, plant exudates help create and sustain anaerobic conditions, resulting in a renewable source of hydrogen as electron donors for dehalorespirers (Eberts et al, 2005). However, previous studies have showed that plant roots can release phenolic substances to stimulate the growth of polychlorinated biphenyls (PCBs) degrading bacteria (Fletcher and Hegde, 1995;Leigh et al, 2006).…”
Section: Hexachlorobenzenementioning
confidence: 99%
“…In this case, the presence of plants and their release of root exudates could potentially render the groundwater anoxic and support reductive dechlorination (Eberts et al 2005). The interest in gas transport in plants that remove groundwater from contaminated aquifers is twofold.…”
Section: Plants Gases and Groundwatermentioning
confidence: 99%
“…Many of these processes of diffusion gas transport have not been examined in poplar trees, however, and such studies would shed light on how poplar trees can use groundwater rendered anoxic due to high levels of contamination (Eberts et al 2005). …”
Section: Plants Gases and Groundwatermentioning
confidence: 99%